The differential role of magnetic resonance imaging in predicting surgical outcomes between children versus adults with temporal lobe epilepsy - Xu, Ke; Wang, Xiongfei; Zhou, Jian; Guan, Yuguang; Li, Tianfu; Luan, Guoming (Frontiers in Neuroscience, 2022)
Objective: This study aims to investigate the clinical discrepancies, and the different predictors of anterior temporal lobectomy (ATL) in children (< 18 years at surgery) and adults (> 18 years at surgery) with temporal lobe epilepsy (TLE). Methods: A total of 262 patients (56 children, 206 adults) with TLE who underwent ATL were included in this study. The clinical variables, including patients’ characteristics, preoperative evaluations, pathology, surgical prognosis, and surgical predictors were assessed the discrepancies between TLE children versus adults using univariate and multivariate analyses. Kaplan-Meier survival analysis was used to calculate the probability of seizure freedom and AEDs withdrawal after ATL, and the difference between TLE children and adults was analyzed using Log-Rank test. Results: There were significant differences including semiology, magnetic resonance imaging (MRI) examinations, numbers of preoperative AEDs, and pathologies between TLE children and adults (P < 0.05, Q < 0.05). The MRI-detected epileptic focus was the only independent predictor of seizure freedom (P = 0.002, Q = 0.036) in TLE children, and the concordance of MRI-detected focus with video-electroencephalography (video-EEG)-detected epileptic zone was the only variable associated with seizure freedom in TLE adults (OR 2.686, 95% CI 1.014–7.115, P = 0.047). The TLE children experienced a higher probability of AEDs withdrawal than adults after surgery (P = 0.005). Significance: There were remarkable differences in clinical manifestations, MRI examinations, number of preoperative AEDs, and pathologies between TLE children versus adults. TLE children had a higher possibility of AEDs withdrawal than adults after surgery. The favorable seizure outcome of ATL depended on the early complete resection of MRI-detected epileptogenic focus in TLE children, while the concordance of MRI-detected focus with EEG-detected epileptogenic zone was the predictor of favorable seizure outcomes in TLE adults.